Otimização por funções representáveis como a diferença entre funções convexas com aplicação em um problema de arranjo físico - Fernandes, Manoel de Pontes (2012)
Programming problems which each function can be represented as a diference of two convex function are called DC programming problems and represent a wide range of applications. In this work, DC programming is used do model and solve the proposed layout problem. Here we present the teory of DC optimization problems and some applications which we will see with more details further for better understanding of the teory. Also is proposed a model for the layout problem, modeled mathematically, further represented as a DC optimization problem and finally, placed in its canonical form (CDC). Its done because the DC structure is closed in many operations commonly found in optimization problems, unlike a convex function, which does not preserve its structure by a simple scalar multiplication. Finally, an algorithm is proposed to solve the layout problem. This problems are of great importance in engineering because, in the real world, changes in the layout are usually costly, time consuming and may even unfeasible, depending on the project. Thus, the objective of this work is to solve the proposed layout problem put in the C.D.C. form, through an algorithm, motivated by the need for optimization of the use of the space, in the general sense of the word.